Витые и ложновитые шейные украшения из мастерских боспорских торевтов - Бабенко, Л.И. (Археологія і давня історія України, 2019)
В статье рассматриваются особенности конструкции и погребального контекста витых и ложновитых шейных украшений, изготовленных в мастерских Боспора. For now five neck or pectoral ornamentals are known that have twisted or falsely twisted binders, which were made in the workshops of the Bospor jewelers. The binders construction is represented by three types which are different in their structure. The torque from the primary burial Kul-Oba is related to the first type. Its binder consisted of the twisted bronze pivot covered by a thin golden sheet, which followed the binder shape. The binders of the ornamentals of the second type represent a hollow pipe, which relief imitated the six round pivots spiral twisting (the torque from Solokha, the pectoral from the Tolstaya Mogila). The ornamentals of the third type have a binder that is made of twisted pipes or wires (the torque from the Kul-Oba, the pectoral from the Bolshaya Blyznitsa). The first four ornamentals can be the products of the same workshop, and they can be made by the jewelers of two or three generations. The craftsman who made the pectoral from the Bolshaya Blyznitsa was most likely working in another workshop. On the basis of the burial context, the torques (pectorals) with a massive twisted/falsely twisted binder can be considered as one of the markers of royal dignity of its owner.